Metabolic reprogramming and epithelial‐to‐mesenchymal transition in cancer. (21st May 2017) - Sciacovelli, Marco; Frezza, Christian
Abstract : Several lines of evidence indicate that during transformation epithelial cancer cells can acquire mesenchymal features via a process called epithelial‐to‐mesenchymal transition (EMT). This process endows cancer cells with increased invasive and migratory capacity, enabling tumour dissemination and metastasis. EMT is associated with a complex metabolic reprogramming, orchestrated by EMT transcription factors, which support the energy requirements of increased motility and growth in harsh environmental conditions. The discovery that mutations in metabolic genes such as FH, SDH and IDH activate EMT provided further evidence that EMT and metabolism are intertwined. In this review, we discuss the role of EMT in cancer and the underpinning metabolic reprogramming. We also put forward the hypothesis that, by altering chromatin structure and function, metabolic pathways engaged by EMT are necessary for its full activation. Abstract : During transformation, epithelial cells undergo a complex phenotypic reprogramming called epithelial‐to‐mesenchymal transition (EMT), whereby they become more motile and invasive. During EMT, cancer cells also profoundly reprogramme their metabolism. In this review, we describe the molecular underpinnings of the metabolic rewiring during EMT and how, in turn, metabolic alterations can trigger EMT.